(untitled) (Nigerian Journal of Physiological Sciences, 2021)
This study evaluates the therapeutic potentials of selected antihypertensive drugs [valsartan, amlodipine, lisinopril and their fixed-dose combinations (amlodipine + lisinopril) and (valsartan + lisinopril)] in ameliorating trastuzumab (TZM)‑induced cardiac dysfunctions in experimental rats. After an ethical clearance for the study was obtained, in-bred young adult female Wistar rats were randomly allotted into 10 groups of 6 rats per group. Group I rats were treated with 10 ml/kg/day sterile water p.o. and 1 ml/kg/day sterile water i.p.; Group II, III and IV rats were orally treated with 5 mg/kg/day VAL and 1 ml/kg/day sterile water i.p., 0.25 mg/kg/day ADP and 1 ml/kg/day sterile water i.p., 0.035 mg/kg/day LSP and 1 ml/kg/day sterile water i.p., respectively. Group V rats were orally pretreated with 10 ml/kg/day of sterile water before i.p. 2.25 mg/kg/day of TZM. Groups VI-VIII rats were equally pretreated with 5 mg/kg/day VAL, 0.25 mg/kg/day ADP, and 0.035 mg/kg/day LSP before i.p. 2.25 mg/kg/day TZM treatment, respectively. Also, Groups IX and X rats were orally pretreated with the fixed-dose combinations of 0.25 mg/kg/day ADP + 0.035 mg/kg/day LSP in dissolved in sterile water and 5 mg/kg/day VAL + 0.035 mg/kg/day LSP before 2.25 mg/kg/day TZM treatment for 7 days. Blood pressure parameters [systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial blood pressure (MAP)] and electrocardiogram (ECG) of the treated rats were measured using non-invasive procedures on days 1 and 7 of the experiment, following which the treated rats were sacrificed humanely under light inhaled diethyl ether and histopathological examination was conducted on all treated rat hearts. Results show that repeated TZM treatment significantly (p<0.05) raised SBP, DBP and MAP values from 115.0 ± 17.1 mmHg, 85.1 ± 15.1 mmHg and 94.7 ± 15.5 mmHg, respectively on day 1 to 127.7 ± 27.8 mmHg, 87.4 ± 27.3 mmHg and 100.5 ± 26.4 mmHg, respectively, on day 7. Oral pretreatments with VAL, ADP, LSP and their fixed-dose combinations significantly (p<0.05) attenuated increases in the SBP, DBP and MAP values with the most significant attenuation mediated by the fixed-dose VAL + LSP combination at the SBP, DBP and MAP values of 103.8 ± 20.6 mmHg, 65.5 ± 18.8 mmHg, and 77.9 ± 18.7 mmHg, respectively. TZM treatment also profoundly (p<0.05) prolonged the QT and corrected QT intervals from 85.0 ± 11.5 ms and 161.6 ± 20.3 ms, respectively, on day 1 to 110.2 ± 21.5 ms and 226.5 ± 41.5 ms, respectively, on day 7. However, these QT and corrected QT interval prolongations were effectively and profoundly attenuated by oral pretreatments with VAL, ADP, LSP and their fixed-dose combinations. In addition, TZM cardiotoxicity was characterized by marked vascular and cardiomyocyte congestion and coronary artery microthrombi formation. However, these histopathological changes were reversed with oral pretreatments with ADP, LSP, VAL and fixed-dosed [(ADP + LSP) and (VAL + LSP)] combinations although fixed-dose VAL + LSP was associated with histopathological lesions of coronary arterial wall cartilaginous metaplasia. Overall, this study revealed the promising therapeutic potentials of VAL, ADP, LSP and their fixed-dose combinations as repurposed drugs for the prevention of TZM-mediated cardiac dysfunctions